From immune checkpoints to therapies: understanding immune checkpoint regulation and the influence of natural products and traditional medicine on immune checkpoint and immunotherapy in lung cancer - Zhou, Yibin; Wang, Fenglan; Li, Guangda; Xu, Jing; Zhang, Jingjing; Gullen, Elizabeth; Yang, Jie; Wang, Jing (Frontiers in Immunology, 2024)
Lung cancer is a disease of global concern, and immunotherapy has brought lung cancer therapy to a new era. Besides promising effects in the clinical use of immune checkpoint inhibitors, immune-related adverse events (irAEs) and low response rates are problems unsolved. Natural products and traditional medicine with an immune-modulating nature have the property to influence immune checkpoint expression and can improve immunotherapy’s effect with relatively low toxicity. This review summarizes currently approved immunotherapy and the current mechanisms known to regulate immune checkpoint expression in lung cancer. It lists natural products and traditional medicine capable of influencing immune checkpoints or synergizing with immunotherapy in lung cancer, exploring both their effects and underlying mechanisms. Future research on immune checkpoint modulation and immunotherapy combination applying natural products and traditional medicine will be based on a deeper understanding of their mechanisms regulating immune checkpoints. Continued exploration of natural products and traditional medicine holds the potential to enhance the efficacy and reduce the adverse reactions of immunotherapy.